An Economic Study of Biokraft From Mixed of Trunk and Branch Wastes of Mangium on Several Pulping Process Conditions - Devi Silsia; Ridwan Yahya; Mucharromah Mucharromah; Jerry Antonio (Jurnal Ilmu Kehutanan)
Addition of P. chrysosporium fungus on chip mixture of mangium trunk and branch before pulping process could increase the efficiency of chemical used, save energy consumption and improve the quality of effluent. Before application in the pulp industry, it should be made sure that biokraft method of mangium trunk and branches mixture is economically feasible. This study aims to determine the proper biokraft process applied to the pulp industry. In this study, costs incurred from biokraft modified cooking methods (chemical reduction, energy reduction and the combination of chemicals and energy reduction) were calculated, capitalized and then compared with the cost incurred from conventional kraft process.The results showed that biokraft method with modifications on energy reduction was economically feasible to be applied in pulp industry because it has the smallest CC/ton of pulp (Rp. 50,952,915.15 /ton of pulp) on condition that an increase of biopulping operating cost is in the range of 5-30%.